Controle dos comunicantes: sua interferencia na situação epidemiologica da hanseníase - PEDRAllANI, Elisete Silva (1986)
The control situation of hanseniasis patients' contacts needs a deeper study which would show the reality in the public health centers and their consequence over the whole country. The increasing of the prevalence rate of the disease added to the bad social-economic conditions of the patients and contacts gave us subsidies to important studies to understand the present epidemiological picture. This research had the purpose of diagnosing the control situation of hanseniasis patients contacts in a public health center which had, at the moment of this research (1983) 160 hanseniasis patients (incidence of 1.2/1000) and 757 contacts registered in a Subprogram of Hansen's Disease Control.